ПРОБЛЕМИ ПОШУКУ БАРОКОВОГО ОБРАЗУ У СЛОБОЖАНСЬКОМУ ІКОНОПИСІ (Педагогіка вищої та середньої школи, 2006)
This article up the problem of formation of Baroque's aesthetics in Slobotuhumi's icon-painting and combination both Dezantinesque and West-European influence in the local icon-painting. The author outlines characteristic paintings peculiar, tigs increasing of emblematic and symbolism at icon - pointing topics.